Teater for alle? Norsk teaterpolitikks ambisjon – og organisatoriske og kunstneriske konsekvenser - Nygaard, Jon (Peripeti, 2009)
The ambition of the Norwegian government is to establish Norway as a leading cultural nation and to make art of high artistic quality accessible for all. The new theatre in the county Akershus, surrounding Oslo, will achieve this ambition through a decentralized organization and an artistic program based on local identity and that the impulse and repertory of the theatre comes from its audience.